The future of tourism: an interview with Dr Daniel Wright about the genre of science fiction - Ian Seymour Yeoman; Daniel William Mackenzie Wright (Journal of Tourism Futures)
Purpose – As the Journal of Tourism Futures celebrates its 10th Anniversary, Dr Ian Yeoman (Hotel Management School Leeuwarden) interviews Dr Daniel Wright (University of Central Lancashire) about the future genre of science fiction and his publications. Design/methodology/approach – A personal interview. Findings – Science fiction research is about asking difficult questions, the questions we feel uncomfortable asking and answering. Science fiction is a powerful medium to imagine the future, which students love as it is provocative. In the interview, Dr Wright reflects upon his own writing from immortality to the end of the world. Originality/value – The power of science fiction, as a genre of transformation, skepticism and thinking out of the box, is often missing in futures studies and scenario planning.